(untitled) (Journal of Pharmaceutical Negative Results, 2023)
An individual's financial stability and instability are significantly influenced by their level of financial literacy. For their future, young people need to have a thorough awareness of economic issues. In the context of a developing economy like India, where there are no post-retirement benefits as in many industrialised nations, this is of utmost importance. Ability needs to be built up. To make wise financial decisions, students must be financially literate. Teachers, classmates, school buddies, and parents can help to foster financial literacy at home. Teachers, classmates, school buddies, and parents can help to foster financial literacy at home. 95 parents, 418 students from were also questioned (National Capital Territory) of Delhi in addition to this to get their viewpoint. The questionnaire method was used to collect the main data. It has been demonstrated that students are motivated to improve their financial literacy. Additionally, it was shown that both parents and instructors influence how their students view money. It was shown that giving quizzes and letting students participate in different financial games had a big impact on their financial attitudes.